Bimolecular reactions of the dications and trications of atoms and small molecules in the gas-phase. Issue 1 (6th February 2017) - Price, Stephen D.; Fletcher, James D.; Gossan, Felicity E.; Parkes, Michael A.
Abstract: This review discusses the recent developments in our understanding of the electron transfer and bond-forming reactions of small atomic and molecular dications in the gas-phase. A summary of the properties of isolated dications is presented, followed by a review of the major experimental techniques used to probe dicationic reactivity. Electron transfer reactions of dications with neutral species are then discussed, including recent rationalisations of this class of reactivity using simple electrostatic models. Our current understanding of the reactions of dications with neutral atoms and molecules which result in the formation of new chemical bonds is then presented. This part of the account is built around three case studies, including some new results on the bond-forming reactions of with CH4 . Moving beyond dicationic species, the account then discusses recent results concerning the bond-forming reactivity of tricationic atoms and small molecules. This section includes the mechanistic conclusions drawn from the first results involving the coincident detection of all three positively charged species generated from the reaction of a molecular trication: + O2 → SO + + CS +  + O + . The review concludes with some thoughts concerning the future development of the field.